2018
DOI: 10.1108/ijsi-12-2017-0075
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of aeronautical composites containing self-healing microcapsules

Abstract: Purpose Over the last decades, self-healing materials based on polymers are attracting increasing interest due to their potential for detecting and “autonomically” healing damage. The use of embedded self-healing microcapsules represents one of the most popular self-healing concepts. Yet, extensive investigations are still needed to convince on the efficiency of the above concept. The paper aims to discuss these issues. Design/methodology/approach In the present work, the effect of embedded self-healing micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…However, it can be seen from Figure 21 that the curve for the model with a diameter of 1 μm reaches the highest failure load values, whereas that for the 10% volume content also reaches very high values. In contrast, the lowest load value and, consequently, the lowest ILSS were observed in the material with the highest microcapsule diameter (3 μm) and the material with the highest microcapsule volume content (26%), which is consistent with other studies (Polydoropoulou et al , 2018; Nassho and Sanada, 2020). Therefore, our results indicate that both the larger microcapsules and the numerically higher volume content inside the material are detrimental to its strength values, as a reduction of 14% was observed for the highest diameter value and of 10% for the highest microcapsule volume content tested.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, it can be seen from Figure 21 that the curve for the model with a diameter of 1 μm reaches the highest failure load values, whereas that for the 10% volume content also reaches very high values. In contrast, the lowest load value and, consequently, the lowest ILSS were observed in the material with the highest microcapsule diameter (3 μm) and the material with the highest microcapsule volume content (26%), which is consistent with other studies (Polydoropoulou et al , 2018; Nassho and Sanada, 2020). Therefore, our results indicate that both the larger microcapsules and the numerically higher volume content inside the material are detrimental to its strength values, as a reduction of 14% was observed for the highest diameter value and of 10% for the highest microcapsule volume content tested.…”
Section: Resultssupporting
confidence: 91%
“…The reinforcement required for the second part of the simulation process was modeled as a plain weave of carbon fibers of the company Teijin and, in fact, the Toho Tenax-E HTA40/E13/3 K/200tex. The properties were collected from the product data sheets of the company, as well as MatWeb (Polydoropoulou et al , 2018). The material properties are listed on Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The authors have already demonstrated through a numerical procedure based on finite elements how to describe the behavior of the single ply (Viscardi, Arena, Barra and Guadagno, 2016). Other authors (Polydoropoulou, Katsiropoulos, Loukopoulos and Pantelakis, 2017; Polydoropoulou et al , 2018) have worked to investigate the static performance of self-healing resin: so remarkable self-repairing efficiency (of almost 115 percent) was achieved for the filled material in the case of 90 percent preloading. Numerical simulations have demonstrated that micro-cracks developed during the testing as well as during the manufacturing process may have been filled by the polymerized healing agent.…”
Section: Self-healing Materialsmentioning
confidence: 99%
“…This kind of self-responsive resins can manifest a very interesting applicative potentiality. Recently, the authors have worked to investigate the static performance of aeronautical self-healing resin: a remarkable self-repairing efficiency was achieved in the case of 90 percent preloading (Polydoropoulou, Katsiropoulos, Loukopoulos and Pantelakis, 2017a, b).…”
Section: Introductionmentioning
confidence: 99%